MALARIA SEREBRAL - Kiking Ritarwan* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION CEREBRAL MALARIA IS THE MOST SEVERE NEUROLOGICAL COMPLICATION OF PLASMODIUM FALCIFARUM IT OCCURS IN ABOUT 12 IN PATIENTS INFECTED WITH PLASMODIUM FALCIFARUM AND THE MORTALITY IS STILL HIGH